The school library and shifting paradigms : folio - Reid, Derek, 1954- (1998)
Thesis (M. Ed.)--Memorial University of Newfoundland, 1998. Education Bibliography: leaves 112-120 Educational restructuring is changing curriculum, instructional design, and classroom practices. In today's learning environment, students are actively engaged in their learning, enabled by access to a vast array of multi-sensory resources. One of the driving forces behind this change is technology, and educators must begin to use the tools provided by it or the future may overcome them. -- A radical change, in philosophy and conception, brought about by technology, is also altering the environment of the school library resource centre, its programs, and the role of teacher-librarians to more accurately reflect the environment in which they function. The increase in electronic and interactive media has transformed the school library resource centre from a repository of books to an information technology centre. A new information literacy has evolved to access, analyze, apply, create, and communicate that information. The teacher-librarian no longer manages a collection, but rather integrates technology into the curriculum through cooperatively planned and taught units of study. -- School library resource centres and their programs, as well as teacher-librarians who have not kept pace with these changes or constructed a vision for thefuture, may not be empowering students to be independent, life-long learners.